TI_GERICHTE 12.2016.13 vom 18. Mai 2017 , Legittimazione attiva - giudizio preliminare ex art. 181 CPC/TI - carattere vincolante - TI Tribunale d'appello (2017)
Legittimazione attiva - giudizio preliminare ex art. 181 CPC/TI - carattere vincolante